From land reform to pump energisation: a shift in agricultural drivers in West Bengal [Abstract only] - Mitra, Archisman; Buisson, Marie-Charlotte (2014)
Introduction and objectives: West Bengal is one of the few Indian states which implemented land reforms, called “Operation Barga” in 1978. The spectacular agricultural growth witnessed in the 1980’s and early 1990’s is attributed by many in the literature to Operation Barga. Nevertheless, it has not been the sole driver of this growth. Indeed in West Bengal, pump electrification rate for groundwater irrigation follows a very similar trajectory as the agricultural growth rate. Our purpose is to estimate the extent to which pump electrification has contributed towards West Bengal’s agricultural growth, by providing farmers a cost effective way (compared to diesel) to access groundwater. Methodology approach: Based on secondary data from government sources we built a 14 years panel database for 15 districts of West Bengal. Therefore, our approach uses inter-district and yearly variations in the pump electrification rate to measure its effect on agricultural productivity. Our main empirical results are based on regression analysis at the district level. The impact of pump electrification rate is estimated on rice (Aman and Boro) yields and areas, controlling for other timevarying variables including input use, rainfall, road-access, and land-reform. We also examine the trends in groundwater level to understand the sustainability of pump energisation and agricultural growth. Analysis, results, conclusions and recommendation: The results indicate the positive and significant effect of pump electrification on agricultural output and areas over the period from 1994-2007. By this time, Operation Barga had reached a peak and the intensity of land reform in the State was stagnant. Indeed, pump energisation took over land reform as a driver of agricultural growth. We note that the effect of pump energisation is more pronounced for boro cultivation which is a water intensive crop cultivated in the dry season and thus requiring intensive irrigation. This result argues that pump electrification (with an advantageous flat tariff rate before 2007) improved the physical and economical access to the water market, which in turn made boro cultivation viable for a lot of farmers. In a context where in West Bengal, most farmers are small and do subsistence farming, increased boro production goes a long way in ensuring food security for millions of poor farmers. These results are of particular interest in view of the recent changes in West Bengal’s policy of groundwater use. First in 2007, the tariff structure of agricultural electric connections has been changed from a flat to a metered tariff. Then starting in 2011, getting electric connection for irrigation purposes had been made easier through the removal of administrative permit requirement in areas with sustainable water tables and through a subsidy for the investment cost. These policies are in parallel accompanied by a new boost in the number of pumps electrified since 2007. Recognising the role of pump electrification in the agricultural growth history of West Bengal therefore helps us to understand the potential impact of these new policies.